COMPARATIVE STUDY OF WATER CONTENT AND SENSORY QUALITY OF SALTED LEMURU FISH (Sardinella lemuru) WITH DIFFERENT SALTING METHODS - Dewi, Resti Nurmala; Iksan, Muhammad (Chanos Chanos, 2025)
Salting is one of the most widely used traditional preservation methods for producing salted fish, including lemuru (Sardinella lemuru). However, scientific information regarding the effect of different salting techniques on the water content and sensory characteristics of salted lemuru remains limited. This study aims to compare the water content and sensory quality of salted lemuru processed using wet salting (50% and 100%) and dry salting (5% and 10%) with different drying durations (5, 7, and 9 hours). The production process followed the Indonesian National Standard SNI 8273:2023, while moisture analysis referred to SNI 2354.2:2015. Sensory evaluation was conducted by 30 untrained panelists assessing appearance, odor, and texture. Results showed that dry salting produced lower moisture content (7.22-8.27%) compared to wet salting (9.52-11.41%). In contrast, the highest appearance and texture sensory scores were obtained from wet salting, particularly treatment B100-9 (score 8.60), whereas dry salting with high salt concentration and prolonged drying (K10-9) resulted in decreased texture and odor quality due to excessive dehydration. Overall, the findings confirm that salting method significantly affects the final quality of salted lemuru, and wet salting with an optimal salt concentration provides the best balance between moisture reduction and desirable sensory characteristics.